Legal Consequences Of Breach Of Contract In Mobile Phone Sale And Purchase Agreements (A Study Of Malang District Court Decision Number 149/Pdt.G/2023/PN.Mlg) - Michella Martiza Matondang; Syaiful Khoiri Harahap; Zetria Erma (CV. Era Digital Nusantara, 2026)
Technological growth in Indonesia is advancing rapidly as public demand for communication devices increases, driving significant growth in the mobile phone market—both online and offline. However, the high demand for quality technology has led to the emergence of disputes in mobile phone sales. This is exemplified by the Malang District Court Decision Number 149/Pdt.G/2023/PN.Mlg regarding a sales agreement between PT. Sentral Global Mitra Sejahtera and FitraArdhitaNurullisha Putra, in which the debtor defaulted. Based on this, the author focuses the research as follows: 1) Factors causing breach of contract in mobile phone sales agreements; 2) How judges consider the case when adjudicating mobile phone sales agreements; and 3) The legal consequences of breach of contract in mobile phone sales agreements. The type of research used is normative legal research, which involves analyzing, observing, and examining legal materials obtained from primary, secondary, and tertiary sources. The results of this study indicate that the legal consequences of breach of contract in a mobile phone sales agreement, as seen in Malang District Court Decision Number 149/Pdt.G/2023/PN.Mlg, arose due to the defendant’s delay in making the final payment to the plaintiff, even though the plaintiff had attempted to contact the buyer personally. The plaintiff also attempted to issue a formal notice, but the defendant did not demonstrate good faith. The defendant, having been found in breach of contract, must pay the plaintiff the sum of IDR146,594,500.00, as well as court costs amounting to IDR 267,700.00.